Vibration assisted machining theory, modelling and applications - Zheng, Lu (John Wiley & Sons, Inc., 2021)
"Vibration Assisted Machining: Theory, Modelling and Applications comprehensively covers all key aspects of vibration assisted machining such as cutting kinematics and dynamics, effect of workpiece materials and wear of cutting tools and applications. Case studies with detailed guidance on design, modelling and tests of VAM systems, and machining experiment method are included and state-of-the-art research development on cutting force modelling and surface texture generation is considered. Vibration Assisted Machining: Theory, Modelling and Applications provides engineering students, researchers, and manufacturing engineers with the fundamentals of vibration assisted machining and methodologies for developing and implementing such technology to solve practical industry problems"-- Provided by publisher.